Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve for x. -5(-x - 4) - 3x – 5 = 13

Sagot :

Given the following equation:

[tex]-5\mleft(-x-4\mright)-3x-5=13​[/tex]

You can solve for the variable "x" by following the steps shown below:

Step 1. Apply the Distributive property by multiplying eact term inside the parentheses by -5:

[tex]\begin{gathered} (-5)(-x)-(-5)(4)-3x-5=13​ \\ 5x+20-3x-5=13 \end{gathered}[/tex]

Step 2. Add the like terms on the left side of the equation:

[tex]2x+15=13[/tex]

Step 3. Apply the Substraction property of equality by subtracting 15 from both sides of the equation:

[tex]\begin{gathered} 2x+15-(15)=13-(15) \\ 2x=-2 \end{gathered}[/tex]

Step 4. Finally, apply the Division property of equality by dividing both sides of the equation by 2:

[tex]\begin{gathered} \frac{2x}{2}=\frac{-2}{2} \\ \\ x=-1 \end{gathered}[/tex]

The answer is:

[tex]x=-1[/tex]

Did you understand?